The Increased Likelihood of Diarrhea in Older Population: Result of a Household Health Survey in Laha Village, Ambon City - Christiana Rialine Titaley; Fadila Tri Starlia; Cokorda Istri Arintha Devi; Juen Carla Warella; Josepina Mainase; Maxwell Landri Vers Malakauseya; Noviyanter Siahaya; Etrin Zulqarnain Eka Saputra Linggar; Augie Desvie Klausya Kadun (Future Science, 2023)
Diarrhea is defined as three or more liquid bowel movements in one day. Apart from being a cause of high morbidity and mortality in infants and toddlers, diarrhea is also a health problem in the elderly, especially in developing countries like Indonesia. This study aimed to analyze factors related to diarrheal in the people of Laha Village, one of the coastal villages in Ambon City. The data were derived from a household health survey carried out in the coastal area of Laha Village in November 2022. The dependent variable in this analysis was diarrhea. The independent variables were demographic status, sanitation, dietary patterns, and other diarrhea-related problems. Data analysis used a multivariate logistic regression method. The results of this study showed that the prevalence of diarrhea in Laha Village was 9.5%. Diarrhea was found in infants, children, young adults, and the elderly. We found a significant association between diarrhea and respondents aged >60 (aOR=3.6; 95CI%: 1.04-12.8; p=0.043). Although not significant, the percentage of diarrhea cases was higher in people who did not use latrines for defecation (11.8%) compared to people who used latrines (9.1%). These results indicate the need to conduct regular diarrhea prevention programs to prevent diarrhea, particularly for the elderly, in addition to efforts to improve hygiene and sanitation in the community.